Oil Palm Roots Architecture in Response to Soil Humidity - Yazid Ismi Intara; Abimanyu Dipo Nusantara; Supanjani Supanjani; Zulbahrum Caniago; Riska Ekawita (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2018)
Oil palm (Elaeis guenesis) is one of the most important estate crop commodities in Indonesia. The root is one of the plant organs which plays a vital role in plant growth and palm oil production. The objective of this research was to determine the architecture of oil palm roots in response to soil humidity in the root zone in its initial water footprint system. Destructive and non-destructive methods were used to determine the roots’ parameters, i.e. root depth, root length and root density of oil palm age of mature plants. The result showed that depending on the type of the plant material and the soil, oil palm roots could grow horizontally reaching more than 6 m and vertically about 1.5–5 m. Dead primary roots were soon replaced by new ones. Primary roots predominantly served to structurally support the plant so that this root may grow into deeper layers of the soil. Secondary roots generally spread evenly and act as an anchor of the plant body to the ground which in turn strengthen the plant stand. Active horizontal root nets are always renewed with new roots arising from the stem-ends of the palm. The horizontal root nets were located on a radius of 0–1.5 m of a depth of 0–0.4 m, which were very solid for primary, secondary, tertiary and quaternary roots as well as the nets. This condition actively changed the dead roots with new roots. The root mat is very unique, forming a nest mat that can capture and control water availability in the environment of the soil surface around the growing space of oil palm. The architecture of oil palm roots has naturally adapted to form a root system that can conduct a mechanism to maintain soil water balance. The water footprint system was only active at the surface zone (0–0.8 m), while deeper than 0.8 m it was more affected by local aquifer condition.